Using an effective TB vaccination regimen to identify immune responses associated with protection in the murine model - Pinpathomrat, N; Bull, N; Pasricha, J; Harrington-Kandt, R; McShane, H; Stylianou, E (Elsevier, 2021)
A vaccine against tuberculosis (TB), a disease resulting from infection with Mycobacterium tuberculosis (M.tb), is urgently needed to prevent more than a million deaths per year. Bacillus Calmette–Guérin (BCG) is the only available vaccine against TB but its efficacy varies throughout the world. Subunit vaccine candidates, based on recombinant viral vectors expressing mycobacterial antigens, are one of the strategies being developed to boost BCG-primed host immune responses and efficacy. A promising vaccination regimen composed of intradermal (i.d.) BCG prime, followed by intranasally (i.n.) administered chimpanzee adenoviral vector (ChAdOx1) and i.n. or i.d. modified vaccinia Ankara virus (MVA), both expressing Ag85A, has been previously reported to significantly improve BCG efficacy in mice. Effector and memory immune responses induced by BCG-ChAdOx1.85A-MVA85A (B-C-M), were evaluated to identify immune correlates of protection in mice. This protective regime induced strong Ag85A-specific cytokine responses in CD4+ and CD8+ T cells, both in the systemic and pulmonary compartments. Lung parenchymal CXCR3+ KLRG1- Ag85A-specific memory CD4+ T cells were significantly increased in B-C-M compared to BCG immunised mice at 4, 8 and 20 weeks post vaccination, but the number of these cells decreased at the latter time point. This cell population was associated with the protective efficacy of this regime and may have an important protective role against M.tb infection.